Evaluation of effective properties for smart graphene reinforced nanocomposite materials. (2020) - Shingare, K.B.; Gupta, Madhur; Kundalwal, S.I.
Abstract: In this study, analytical and numerical models were developed to investigate the effective properties of graphene reinforced nanocomposite (GRNC) subjected to electromechanical loading. In this analytical mechanics of material (MOM) model was developed to predict effective properties of the composite while numerical finite element (FE) model developed with the help of a representative volume element (RVE). Also, the longitudinal and transverse modulus of GRNC is determined using the Halpin-Tsai equations. Both models are showing a good agreement for loading applied along the fiber direction when compared to transverse loading. The present study highlights on developing efficient NEMS application.